Ensino e pesquisa na estratégia de saúde da família: o PET-Saúde da FMB/UNESP - Cyrino, Eliana Goldfarb [UNESP]; Cyrino, Antonio de Pádua Phiton [UNESP]; Prearo, Alice Yamashita [UNESP]; Popim, Regina Célia [UNESP]; Simonetti, Janete Pessuto [UNESP]; Boas, Paulo José Vilas [UNESP]; Hashimoto, Miriam; Patrício, Karina Pavão [UNESP]; Romanholi, Renata Maria Zanardi [UNESP]; Manuel, Cássia Marisa; Okama, Paula de Oliveira Montandon [UNESP] (FapUNIFESP (SciELO), 2012)
Comprehensive and humanized care provides the underlying principles for the Botucatu School of Medicine (FMB/UNESP) in reorienting health professionals’ training with the development of research and continuing education in the Family Health Strategy. This article analyzed the first year in the Educational Program for Health Work (PET-Saúde) developed by the School of Medicine and the Botucatu Municipal Health Department. The following research themes were selected: oral health in pregnant women, children, and the elderly; immunization in adolescents; health of adults and the elderly; and health and the environment. Workshops were held on the problem-solving methodology, producing intervention models in which students, faculty, and health professionals from local health services were the protagonists. The program is a spin-off of the course on Interaction between the University, Health Services, and the Community, given jointly to the courses in medicine and nursing. There is resistance inside the university, recognizing the devaluation of outpatient clinical practice and primary care. In this process, the PET-Saúde program is intended to strengthen academic practice that links the university with its teaching, research, services, and extension activities to demands from society, in a shared approach.

Tendo como princípios orientadores a integralidade e a humanização do cuidado, a Faculdade de Medicina de Botucatu (FMB) – Unesp busca reorientar a formação dos profissionais de saúde com o desenvolvimento de pesquisas e educação permanente na Estratégia de Saúde da Família. Este artigo analisa o primeiro ano do PET-Saúde desenvolvido na FMB e Secretaria Municipal de Saúde de Botucatu (SP). Foram selecionados como temas de investigação: saúde bucal de gestante, criança e idoso; imunização do adolescente; saúde do adulto e do idoso; e saúde e meio ambiente. Realizaram-se oficinas com a metodologia da problematização, produzindo-se modelos de intervenção nos quais alunos, docentes e profissionais de saúde dos serviços locais de saúde são protagonistas. O programa é um desdobramento da disciplina Interação Universidade, Serviço e Comunidade, ministrada de modo integrado aos cursos de Medicina e Enfermagem. Há resistências no interior da universidade, reconhecendo-se a desvalorização da prática clínica extra-hospitalar e na Atenção Básica. Nesse processo, o PET-Saúde vem fortalecer a prática acadêmica que interliga a universidade, em suas atividades de ensino, pesquisa, serviço e extensão, com demandas da sociedade, de forma partilhada.
Teaching and research in the family health strategy: the educational program for health work at the Botucatu School of Medicine/Unesp
Keywords: Medical education; Nursing education; Primary health care; Family health; Health education; Education, continuing; PET-Saúde; Educação médica; Educação em enfermagem; Atenção primária à saúde; Saúde da família; Educação em saúde; Educação continuada; Programa de educação pelo trabalho